AN ANALYSIS OF ENGLISH MODALS IN MODAL VERB PHRASE STRUCTURES IN EDUCATIONAL ESSAYS OF ‘SHERRY JOHNSON’ AND ‘TAMJID MUJTABA’ - Ikrar Genidal Riadil (Jurnal Pendidikan Bahasa, 2020)
AbstractThis research aimed to present the findings of English modals in modal verb phrase structures in educational essays of ‘Sherry Johnson’ and ‘Tamjid Mujtaba’, which to increase the learners’ awareness of modals when they hesitate in the foreign language, which is the very common in writing. This research used qualitative research to analyze the modal verb phrase in educational essays of ‘Sherry Johnson’ and ‘Tamjid Mujtaba’. This research has found that the most frequent modal verbs in these essays are can, may, will, should, would, and must. The researchers found 23 different modal verbs in ‘Sherry Johnson’ and ‘Tamjid Mujtaba’ academic essays documents that indicate actions, states and conditions associated with education. The most used modals were in ‘Tamjid Mujtaba’ essay, it produced 12 modals. These results correspond with the definition of these documents. The findings are proofing of how language expresses the characteristics of an academic text type in a professional and academic way domain.